Analisis Laporan Realisasi Anggaran Pendapatan Daerah pada Pemerintah Kota Malang Tahun 2021 – 2023 - Anastasya Amara Salsabila; Sonny Fransisco Siboro; Yunita Tri Damayanti; Fitrah Sarah Maryanti (Pusat Riset dan Inovasi Nasional, 2024)
This study analyzes the Regional Revenue of the Malang City Government for the 2021-2023 Fiscal Year based on the Budget Realization Report. This research uses quantitative description analysis with the concept of financial ratio calculation. Secondary data from the official website of the Malang City Government, https://malangkota.go.id, is used to calculate these financial ratios. The method is carried out by considering the performance indicators of regional financial management of the Malang City Government using five indicators: 1) Revenue Budget Variance Analysis 2) Financial Ratio Analysis of Degree of Decentralization 3) Regional Financial Dependency Ratio 4) Effectiveness Ratio 5) Efficiency Ratio. The results of this study are the Malang City Government is increasingly decentralizing decisions and authority to lower levels. Regional dependence on external assistance is decreasing. There is a change in performance. And the Malang City Government needs efforts to minimize waste, maximize the use of money, and improve organizational efficiency to achieve the desired results.